Fluoxetine suppresses calcium signaling in human T lymphocytes through depletion of intracellular calcium stores. Issue 3 (September 2015) - Gobin, V.; De Bock, M.; Broeckx, B.J.G.; Kiselinova, M.; De Spiegelaere, W.; Vandekerckhove, L.; Van Steendam, K.; Leybaert, L.; Deforce, D.
Graphical abstract